(untitled) (Research, Society and Development, 2021)
The goal of this review was to synthesize the evidence in the literature about the behavioral changes in obese patients after bariatric surgery. A search was carried out on the bases of the Virtual Health Library (VHL) which includes LILACS, MEDLINE, MEDCARIB, P.A.H.O. / W.H.O. (World Healht Organization), PAHO (Pan American Health Organization) and W.H.O.L.I.S. (World Health Organization Library Information System); PubMed; EBSCO; SciELO and Scopus from January 2010 to December 2020. For this search, the combination of the following terms was used: “Bariatric Surgery” OR “Bariatric Surgery” AND “Feeding Behavior” OR “Feeding Behavior”. The original studies were included, the main outcome, the behavioral changes after bariatric surgery in obese patients, written in Portuguese and English. The final analysis was composed of 13 articles. Among these artciles, 84.6% were performed in the last 5 years, 61.5% of the studies used longitudinal designs, predominantly obese patients with the Body Mass Index (IMC) ≥ 35 kg/m2, age range 31 to 52 years and most studies were carried out in Brazil 30.7%, Israel 15.4% and the United Kingdom (15.4%). The changes in eating behavior after bariatric surgery were an increase in snack and candy eaters, food intolerance and altered palatability, difficulty in eating protein and fatty foods. Related to the emotional behavior, there was a change in mood, an increase and / or reduction in depressive and anxiety symptoms, and an increase in impulsivity. As a conclusion, after bariatric surgery, obese patients show changes in eating and emotional behavior.